Assessment of Osteoarthritis Candidate Genes in a Meta‐Analysis of Nine Genome‐Wide Association Studies. Issue 4 (April 2014) - Rodriguez‐Fontenla, Cristina; Calaza, Manuel; Evangelou, Evangelos; Valdes, Ana M.; Arden, Nigel; Blanco, Francisco J.; Carr, Andrew; Chapman, Kay; Deloukas, Panos; Doherty, Michael; Esko, Tõnu; Garcés Aletá, Carlos M.; et al.
<x xml:space="preserve">Abstract</x> Objective To assess candidate genes for association with osteoarthritis (OA) and identify promising genetic factors and, secondarily, to assess the candidate gene approach in OA. Methods A total of 199 candidate genes for association with OA were identified using Human Genome Epidemiology (HuGE) Navigator. All of their single‐nucleotide polymorphisms (SNPs) with an allele frequency of >5% were assessed by fixed‐effects meta‐analysis of 9 genome‐wide association studies (GWAS) that included 5, 636 patients with knee OA and 16, 972 control subjects and 4, 349 patients with hip OA and 17, 836 control subjects of European ancestry. An additional 5, 921 individuals were genotyped for significantly associated SNPs in the meta‐analysis. After correction for the number of independent tests, P values less than 1.58 × 10−5 were considered significant. Results SNPs at only 2 of the 199 candidate genes (COL11A1 and VEGF) were associated with OA in the meta‐analysis. Two SNPs in COL11A1 showed association with hip OA in the combined analysis: rs4907986 (P = 1.29 × 10−5, odds ratio [OR] 1.12, 95% confidence interval [95% CI] 1.06−1.17) and rs1241164 (P = 1.47 × 10−5, OR 0.82, 95% CI 0.74−0.89). The sex‐stratified analysis also showed association of COL11A1 SNP rs4908291 in women (P = 1.29 × 10−5, OR 0.87, 95% CI 0.82−0.92); this SNP showed linkage disequilibrium with rs4907986. A single SNP of VEGF, rs833058, showed association with hip OA in men (P = 1.35 × 10−5, OR 0.85, 95% CI 0.79−0.91). After additional samples were genotyped, association at one of the COL11A1 signals was reinforced, whereas association at VEGF was slightly weakened. Conclusion Two candidate genes, COL11A1 and VEGF, were significantly associated with OA in this focused meta‐analysis. The remaining candidate genes were not associated.